2016
DOI: 10.1021/acsami.6b02361
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Upconversion Emission by Visible-to-Near-Infrared Fluorescent Graphene Quantum Dots for miRNA Detection

Abstract: We developed a sensor for the detection of specific microRNA (miRNA) sequences that was based on graphene quantum dots (GQDs) and ssDNA-UCNP@SiO2. The proposed sensor exploits the interaction between the sp2 carbon atoms of the GQD, mainly π–π stacking, and the DNA nucleobases anchored on the upconversion nanoparticles (UCNPs). This interaction brings the GQD to the surface of the ssDNA-UCNP@SiO2 system, enhancing the upconversion emission. On the other hand, hybridization of the single-stranded DNA (ssDNA) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Table compares the different sensing platforms used for miRNA determination. Compared with other methods, the sensitivity of our biosensor is higher than that of some of the methods and approaches that of certain highly sensitive methods . Additionally, our detection system is time saving (analysis complete within 2 h), cost effective, easy to use, and does not involve the synthesis of nanomaterials or the use of expensive and complex chemical modification techniques.…”
Section: Resultsmentioning
confidence: 98%
“…Table compares the different sensing platforms used for miRNA determination. Compared with other methods, the sensitivity of our biosensor is higher than that of some of the methods and approaches that of certain highly sensitive methods . Additionally, our detection system is time saving (analysis complete within 2 h), cost effective, easy to use, and does not involve the synthesis of nanomaterials or the use of expensive and complex chemical modification techniques.…”
Section: Resultsmentioning
confidence: 98%
“…In 2016, Laurenti et al reported a biosensor using single stranded DNA (ssDNA) and GQDs, which were coupled with the up-conversion nanoparticles (UCNPs) and silica (SiO 2 ) for determining miRNA sequences [94]. The sensor involved the interaction of sp 2 carbon atoms of the GQDs with ssDNA-UCNPs through π-π stacking, which could bring GQDs to the ssDNA-UCNP/SiO 2 surface.…”
Section: Fluorescence-based Gqd Sensorsmentioning
confidence: 99%
“…In the past few years, UCNPs have demonstrated their potential as excellent molecular beacons (MBs) for analytical biomedical applications. Using UCNP materials, a sensor for detection of specific miRNA sequences based on GQDs and UCNP@SiO 2 ‐ssDNA was developed by Laurenti et al The DNA nucleobases anchored on the UCNPs and the GQDs with sp 2 carbon atoms could interact by means of π‐π stacking, which brought the GQD to the surface of the UCNPs@SiO 2 ‐ssDNA system to enhance the upconversion emission. After hybridization of ssDNA chains and target miRNA, the π‐π stacking between UCNPs and GQDs was destroyed, weakening the fluorescence enhancement.…”
Section: State‐of‐the‐art Protocols For High‐quality Mirna Detectionmentioning
confidence: 99%